2006
DOI: 10.2341/05-22
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of Resin Composite Luting Cements to Zirconium Oxide by Two Air-particle Abrasion Methods

Abstract: It was concluded that two different surface conditioning methods and storage conditions did not significantly affect the bonding properties of Panavia F and RelyX Unicem resin composite luting cements to Zirconia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
107
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(125 citation statements)
references
References 17 publications
8
107
0
10
Order By: Relevance
“…However, whereas some of these t reatments have shown good results, 4,6,8,26 other methods have not proven their effectiveness completely. 7,9,20,21,27 In the present study, the application of glass to the ZrO 2 surfaces improved the bond strength between the ceramic and resin cement, regardless of the technique (air blast or gel) or concentration of the gel (15, 25 or 50% of glass by weight). The increase in the bond strength probably occurred due to addition of silica to the surface of the substrate.…”
Section: Discussionmentioning
confidence: 86%
“…However, whereas some of these t reatments have shown good results, 4,6,8,26 other methods have not proven their effectiveness completely. 7,9,20,21,27 In the present study, the application of glass to the ZrO 2 surfaces improved the bond strength between the ceramic and resin cement, regardless of the technique (air blast or gel) or concentration of the gel (15, 25 or 50% of glass by weight). The increase in the bond strength probably occurred due to addition of silica to the surface of the substrate.…”
Section: Discussionmentioning
confidence: 86%
“…A rough surface increases the surface area, improves wettability by reducing surface tension, and creates micromechanical retention. Al 2O3 air abrasion is one of the common methods used to increase surface roughness 8,19,32,33) . Some investigators suggested that superior bonding to zirconia was obtained when with airabraded surfaces [34][35][36][37] .…”
Section: Discussionmentioning
confidence: 99%
“…The morphological pattern obtained with 50-µm aluminum oxide particles was more effective for micromechanical bonding compared to airborne particle abrasion with 100-µm aluminum oxide particles, according to the findings that are consistent with other studies. [15][16][17][18][19][20][21] Using 9.5% hydrofluoric acid etching changed the surface topography of IPS Empress 2 and Cergogold ceramics, creating a topography similar to a honeycomb for Cergogold ( Figure 4C) and elongated the crystals with shallow irregularities for IPS Empress 2 ( Figure 3C). The chemical-etching process can be explained by the preferential reaction of hydrofluoric acid with the silica phase of the feldspathic ceramic to form hexafluorosilicates, which are removed by rinsing with water.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10] The silicate-based ceramic surfaces are etched, often using hydrofluoric acid, which changes its microstructure by dissolution of one of the glassy phases of porcelain and by creating an appropriate microstructure for bonding. [11][12][13][14] Another pre-bonding treatment for ceramic surfaces is airborne aluminum oxide particle abrasion, [15][16] which similarly changes the microstructure of the ceramic surface. The interaction of the luting agent silicate ceramic can be enhanced by the application of a silane coupling agent.…”
Section: Introductionmentioning
confidence: 99%